NET23/STING promotes chromatin compaction from the nuclear envelope. - Poonam Malik; Nikolaj Zuleger; Jose I de las Heras; Natalia Saiz-Ros; Alexandr A Makarov; Vassiliki Lazou; Peter Meinke; Martin Waterfall; David A Kelly; Eric C Schirmer (PLoS ONE)
Changes in the peripheral distribution and amount of condensed chromatin are observed in a number of diseases linked to mutations in the lamin A protein of the nuclear envelope. We postulated that lamin A interactions with nuclear envelope transmembrane proteins (NETs) that affect chromatin structure might be altered in these diseases and so screened thirty-one NETs for those that promote chromatin compaction as determined by an increase in the number of chromatin clusters of high pixel intensity. One of these, NET23 (also called STING, MITA, MPYS, ERIS, Tmem173), strongly promoted chromatin compaction. A correlation between chromatin compaction and endogenous levels of NET23/STING was observed for a number of human cell lines, suggesting that NET23/STING may contribute generally to chromatin condensation. NET23/STING has separately been found to be involved in innate immune response signaling. Upon infection cells make a choice to either apoptose or to alter chromatin architecture to support focused expression of interferon genes and other response factors. We postulate that the chromatin compaction induced by NET23/STING may contribute to this choice because the cells expressing NET23/STING eventually apoptose, but the chromatin compaction effect is separate from this as the condensation was still observed when cells were treated with Z-VAD to block apoptosis. NET23/STING-induced compacted chromatin revealed changes in epigenetic marks including changes in histone methylation and acetylation. This indicates a previously uncharacterized nuclear role for NET23/STING potentially in both innate immune signaling and general chromatin architecture.